Who comes: Yahweh or Nahar? A few remarks on the translation of Isaiah S9:19c-d and the theological meaning of the passage (Part I) - Kruger, H. A. J. (Old Testament essays, 1997)
It is not clear whether the subject of the verb ???? ('come') used in Isaiah 59:19c represents (a characteristic of) Yahweh, 'a divine being', or some other unidentified force. This problem is complicated by the fact that ?? can function as a substantive or an adjective, while ??? can be translated in two quite different ways. The question of whether ???? is derived from ??? or ??? is another obstacle in the way of the exegete. Arguments based on philological grounds alone can probably not solve the translation problems encountered in this text.